EFISIENSI UNIT-UNIT KEGIATAN EKONOMI INDUSTRI GULA YANG MENGGUNAKAN PROSES KARBONATASI DI INDONESIA - SIAGIAN, VICTOR (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
Highly government intervention caused crucial Indonesian sugar market structure. This condition stimulated low productivity, high cost economy, increasing in sugar price and imported sugar. Increased sugar import either legal or illegal must be concerned because international sugar market is thin market and also sugar industry is capital intensive, more over in the beginning of trade liberalization. One of the methods for eliminating imported sugar namely to identified sugar industry efficiency especially carbonatization sugar industry using Data Envelopment Analysis (DEA). DEA calculates relative efficiency to peer unit namely sugar factories in which have highly efficiency score. There are three sugar factories, using carbonatization process, have lowly efficiency score and need input multiplier or reallocation in using input from peer unit.
Keywords: Government Intervention, Sugar Market Structure, Legal and Illegal Import, Thin Market, DEA, Relative Efficiency, Peer Unit.